2015
DOI: 10.1038/srep16477
|View full text |Cite
|
Sign up to set email alerts
|

Reduced cortical microvascular oxygenation in multiple sclerosis: a blinded, case-controlled study using a novel quantitative near-infrared spectroscopy method

Abstract: Hypoxia (low oxygen) is associated with many brain disorders as well as inflammation, but the lack of widely available technology has limited our ability to study hypoxia in human brain. Multiple sclerosis (MS) is a poorly understood neurological disease with a significant inflammatory component which may cause hypoxia. We hypothesized that if hypoxia were to occur, there should be reduced microvascular hemoglobin saturation (StO2). In this study, we aimed to determine if reduced StO2 can be detected in MS usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 31 publications
12
52
0
Order By: Relevance
“…We have identified a striking reduction in cortical tissue StO 2 levels in the frontal cortex of some patients with PBC at rest (Fig. ), similar in magnitude to levels previously reported by us in the frontal cortices of patients suffering with the neuroinflammatory disease MS . In the setting of increased platelet–immune–CEC interactions and altered vessel dynamics discussed above, we propose that hypoxia results from a physical reduction in blood flow through the brain microvasculature, coupled with a local increase in metabolic activity (due to heightened local immune cell activity).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We have identified a striking reduction in cortical tissue StO 2 levels in the frontal cortex of some patients with PBC at rest (Fig. ), similar in magnitude to levels previously reported by us in the frontal cortices of patients suffering with the neuroinflammatory disease MS . In the setting of increased platelet–immune–CEC interactions and altered vessel dynamics discussed above, we propose that hypoxia results from a physical reduction in blood flow through the brain microvasculature, coupled with a local increase in metabolic activity (due to heightened local immune cell activity).…”
Section: Discussionsupporting
confidence: 86%
“…Tight regulation of cerebral blood flow is critical to ensure normal brain oxygenation and function. Cerebrovascular dysfunction and hypoxia have been implicated in a range of neurodegenerative and neuroinflammatory disorders including Alzheimer's disease and multiple sclerosis (MS) . We have shown, using functional MRI, that patients with PBC exhibit alterations in functional hyperemia, although it remains difficult to determine whether alterations in functional hyperemia arise solely from altered brain activity or whether cerebrovascular dysfunction plays a role …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Using quantitative near-infrared spectroscopy, it has been reported that approximately half of MS patients have reduced oxygen saturation in cortical GM [24]. Reduced oxygen saturation is likely to correlate with reduced tissue PO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative near-infrared spectroscopy data indicates that as many as half of MS patients may have hypoxia in the cortex [24]. In EAE mice, MRI measurements sensitive to deoxyhemoglobin provided evidence for hypoxia in the spinal cord [25].…”
Section: Introductionmentioning
confidence: 99%